Pemodelan Overlay Berjenjang Menggunakan Sistem Informasi Geografis sebagai Penentu Daerah Rawan Demam Berdarah - Nurlaila, Gita; Anasi, Putri Tipa; Christanto, Ludovicus Manditya Hari (Jurnal Penelitian Pendidikan Geografi, 2026)
Pontianak Tenggara District is the area with the highest number of suspected cases of Dengue Hemorrhagic Fever (DHF) in Pontianak City. This study uses an overlay method with three levels of vulnerability to map the risk level of DHF spread in Pontianak Tenggara District. The parameters used include environmental indicators such as rainfall, air humidity, air temperature and population density, as well as social indicators such as land use, number of DHF cases, and distance to the river. The results of the study are in the form of a DHF vulnerability map with detailed zoning by village. In general, the overlay results show a vulnerable zone of 46 ha, a moderate zone of 73 ha and a safe zone of 1,423 ha. The vulnerable zone is concentrated in Bansir Laut and Bangka Belitung Laut Villages located on the banks of the Kapuas River. Meanwhile, the safe zone is found in Bansir Darat and Bangka Belitung Darat Villages located far from the river. However, land use in the safe zone still has the potential to influence the spread of DHF. Therefore, the results of this study are expected to be a basis for policy makers in designing effective and efficient DHF control strategies in the future.